2019
DOI: 10.1002/ece3.5876
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and spread of naturally occurring Medea selfish genetic elements in the United States

Abstract: Selfish genetic elements (SGEs) are DNA sequences that are transmitted to viable offspring in greater than Mendelian frequencies. Medea SGEs occur naturally in some populations of red flour beetle (Tribolium castaneum) and are expected to increase in frequency within populations and spread among populations. The large‐scale U.S. distributions of Medea‐4 (M4) had been mapped based on samples from 1993 to 1995. We sampled beetles in 2011–2014 and show that the distribution of M4 in the United States is dynamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…For genetic pest management, these models are useful in predicting the effectiveness of a particular approach before costly constructs and strains are built and field trials are performed. Low-frequency clusters within the United States were identified in our recent survey (Cash et al, 2019), and in an earlier survey, it was clear that M 1 was absent in some geographic areas. In a previous study, we found no evidence of population structure to suggest that these populations are completely cutoff from the rest of the M 1 -bearing populations of the United States (Cash et al, 2019).…”
Section: Models Of Medea and Experiments With Synthetic Medea Constructssupporting
confidence: 48%
See 3 more Smart Citations
“…For genetic pest management, these models are useful in predicting the effectiveness of a particular approach before costly constructs and strains are built and field trials are performed. Low-frequency clusters within the United States were identified in our recent survey (Cash et al, 2019), and in an earlier survey, it was clear that M 1 was absent in some geographic areas. In a previous study, we found no evidence of population structure to suggest that these populations are completely cutoff from the rest of the M 1 -bearing populations of the United States (Cash et al, 2019).…”
Section: Models Of Medea and Experiments With Synthetic Medea Constructssupporting
confidence: 48%
“…Most populations above 33°N were fixed for the element, while most populations sampled below this latitude lacked the M 4 element altogether (Beeman, 2003). Similarly, for the Medea element M 1 , an assessment of beetles collected in 2004-2007 and those collected by us from 2012 through 2014 indicates a patchy distribution within the United States (Cash et al, 2019). Similarly, for the Medea element M 1 , an assessment of beetles collected in 2004-2007 and those collected by us from 2012 through 2014 indicates a patchy distribution within the United States (Cash et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…First reported in the 1920s, natural gene drives have been observed in a variety of organisms, and encompass a variety of different mechanisms: transposable elements 22 that insert copies of themselves at other places in the genome; homing endonuclease genes that copy themselves at targeted genomic sites; segregation distorters 23 that destroy competing chromosomes during meiosis; gamete killers that eliminate gametes not carrying the gene drive; the Medea (maternal-effect dominant embryonic arrest) system that confers maternal-effect lethality to all offspring that does not have a copy of the Medea element; and Wolbachia endosymbionts that favour offspring of infected females (e.g. Beeman et al, 1992;Burt and Trivers, 2006;Sinkins and Gould, 2006;Champer et al, 2016;Agren and Clark, 2018;Collins, 2018;R € udelsheim and Smets, 2018;Cash et al, 2019Cash et al, , 2020Frieb et al, 2019). The study of natural gene drive systems has provided considerable theoretical and empirical insights into how natural gene drives work, how they spread and how simple model predictions on engineered gene drives may fail (Courret et al, 2019;Dyer and Hall, 2019;Finnegan et al, 2019;Larner et al, 2019;Lea and Unckless, 2019;Price et al, 2019;Wedell et al, 2019;Dhole et al, 2020).…”
Section: Mechanisms For Preferential Inheritancementioning
confidence: 99%